KEBIJAKAN STANDARDISASI KESEHATAN DAN KEBERSIHAN DALAM PENGEMBANGAN WISATA KULINER - Kadek Ary Purnama Dewi (Jurnal Yustitia, 2021)
Abstract This study aims to analyze the basic considerations of health and hygiene standardization in the development of culinary tourism and to find the construction of health and hygiene standardization policies in the development of culinary tourism in the future. The basis for the consideration of health and hygiene standardization in the development of culinary tourism is the protection of human rights, where tourism is a human right, and the importance of consuming healthy and clean food and drinks is the right to life and the right to health for humans. This protection is regulated in national and international legal instruments. In fact, the standardization of health and hygiene in the development of culinary tourism is very necessary considering the poisoning cases that have occurred to tourists. The construction of health and hygiene standardization policies in the development of culinary tourism in the future does not only touch business actors at the top level such as serving food in hotels and restaurants, but also on traditional snacks and markets that are culinary tourism destinations. Keywords: policies, standardization, health and hygiene, culinary tourism. Abstrak Penelitian ini bertujuan untuk menganalisis dasar pertimbangan standardisasi kesehatan dan kebersihan dalam pengembangan wisata kuliner dan untuk mengetahui konstruksi kebijakan standardisasi kesehatan dan kebersihan dalam pengembangan wisata kuliner ke depan. Dasar pertimbangan standarisasi kesehatan dan kebersihan dalam pengembangan wisata kuliner adalah perlindungan hak asasi manusia, dimana pariwisata adalah hak asasi manusia, dan pentingnya mengkonsumsi makanan dan minuman yang sehat dan bersih adalah hak untuk hidup dan hak atas kesehatan bagi manusia. Perlindungan ini diatur dalam perangkat hukum nasional dan internasional. Padahal, standarisasi kesehatan dan kebersihan dalam pengembangan wisata kuliner sangat diperlukan mengingat kasus keracunan yang pernah menimpa wisatawan. Konstruksi kebijakan standardisasi kesehatan dan kebersihan dalam pengembangan wisata kuliner ke depan tidak hanya menyentuh pelaku usaha di level atas seperti menyajikan makanan di hotel dan restoran, tetapi juga pada jajanan dan pasar tradisional yang menjadi tujuan wisata kuliner. Kata kunci: kebijakan, standardisasi, kesehatan dan kebersihan, wisata kuliner.